Legal Construction of E-Commerce Income Tax in Online Marketplace: Withholding Tax System Mechanism - Narwadi, Made Wiswarupa; Sadnyini, Ida Ayu (Law Development Journal, 2024)
This legal research aims to answer several legal issues, namely the implications of the emptiness of income tax law with a withholding tax system for online marketplace-based e-commerce and the formulation of income tax legal construction with a withholding tax system for online marketplace-based e-commerce. This study uses normative legal research with an emphasis on conceptual approaches, theories, statutory regulations and the opinion of the author. The research results show that the implications of the vacuum of income tax laws with a withholding tax system for online marketplace-based e-commerce have resulted in suboptimal income tax revenues from online marketplace-based e-commerce business activities. Business actors in the online marketplace do not receive legal protection in the form of convenience in terms of tax administration, which can have an impact on the payment of income tax from business activities in the online marketplace not being optimal in the future. Formulation of future regulations for withholding income tax on online marketplace-based e-commerce using an analogous legal construction method, namely regulating the withholding or collection of income tax as well as the collection of Value Added Tax (VAT) on e-commerce which prioritizes the role of marketplace providers as VAT collectors.